A comparative study to evaluate the efficacy of cisatracurium and rocuronium for endotracheal intubation in pediatric patients: A prospective randomized study - Deepak R,; Seema Shende,; Namrata Jain,; Sanyukta Paul, (Asian Journal of Medical Sciences, 2024)
Background: Cisatracurium and rocuronium are non-depolarizing neuromuscular blockers with an intermediate duration of action and are used safely in short and intermediate-duration surgical procedures in the pediatric population. Aims and Objectives: A prospective randomized study is to assess the efficacy of cisatracurium compared to rocuronium in terms of intubating conditions, clinical duration of action, hemodynamic parameters, and side effects in pediatric patients undergoing surgeries under general anesthesia. Materials and Methods: In this study, 50 patients aged 2–12 years with the American Society of Anesthesiologists grades I and II were randomly allocated into two groups: Group I received injection cisatracurium 0.15 mg/kg IV and Group II received injection rocuronium 0.6 mg/kg IV for intubation. Intubating conditions by Cooper et al., score, TOF count, hemodynamic parameters, signs of histamine release, and complications if any were noted. Results: According to the Cooper et al., score, intubating conditions were excellent in 100% of patients in Group II and 84% of patients in Group I, which was statistically significant. The time required for the first maintenance dose was shorter in Group II (14.04±2.95 min) compared to Group I (20.08±3.68 min). Hemodynamic parameters and demographic profiles were comparable between the two groups. No associated signs of histamine release or any other complications were noted in either group. Conclusion: We concluded that rocuronium 0.6 mg/kg provides better intubating conditions and a shorter duration of action compared to cisatracurium 0.15 mg/kg without any signs of histamine release in pediatric patients.